Acinetobacter guangdongensis Feng et al. 2014 is a junior heterotypic synonym of Acinetobacter indicus Malhotra et al. 2012 - Nemec, Alexandr; Radolfova-Krizova, Lenka (International journal of systematic and evolutionary microbiology, 2017)
A draft whole-genome sequence was obtained for Acinetobacter guangdongensis strain KCTC 42012T and compared against those of the type strains of all Acinetobacter species with validly published names. High similarity was found to Acinetobacter indicus CCM 7832T (average nucleotide identity based on blast and digital DNA-DNA hybridization values of 96.3 and 70.4 %, respectively). In addition, the metabolic, physiological and chemotaxonomic features of KCTC 42012T were shown to be congruent with those of A. indicus. We conclude that Acinetobacter guangdongensisFeng et al. 2014 is a later heterotypic synonym of Acinetobacter indicus Malhotra et al. 2012.
Keywords: rpoB; DNA bakterií; DNA, Bacterial; hybridizace nukleových kyselin; Genome, Bacterial; genom bakteriální; Acinetobacter populi; whole genome; Phylogeny; metabolic and physiological features; ANIb; Acinetobacter; Bacterial Typing Techniques; dDDH; Sequence Analysis, DNA; Nucleic Acid Hybridization; techniky typizace bakterií; sekvenční analýza DNA; fylogeneze